IMPROVING GEOGRAPHICAL KNOWLEDGE IN PRIMARY EDUCATION - Shonazarova Sevara Rashidovna (International Journal of Innovations in Engineering Research and Technology, 2023)
The beginning of the article class It is considered a priority to improve students’ geographical concepts , to integrate new theoretical and practical knowledge about the laws of nature and social development into the educational content, to train creative specialists so that students can acquire knowledge important for social life experiences and various fields of science. coherence between them, i.e. determination of interdisciplinary connections , formation of geographical concepts in elementary school classes , study of geographical events and processes, previously acquired knowledge, skills, and competences in academic subjects and the issues of conscious mastering of educational material by applying competencies in new situations are described.